Bruising as a Forensic Marker of Physical Elder Abuse in Orange County, California, 2006-2008 - Mosqueda, Laura ([Verlag nicht ermittelbar], 2012)
The purpose of the study was to describe bruising as a marker of physical elder abuse. Consenting older adults were examined to document location and size of bruises and assess whether they were inflicted during physical abuse. An expert panel confirmed physical abuse. A research nurse conducted study assessments on 67 adults aged 65 and older reported to Adult Protective Services for suspected physical elder abuse in Orange County, California between July 2006 and May 2008. The study contains a total of 142 variables including age, sex, ethnicity, functional status, medical conditions, cognitive status, history of falls, bruise size, bruise location and color, recall of cause, and responses to the Revised Conflicts Tactics Scales (CTS2) and to the Elder Abuse Inventory (EAI).